Lower Cretaceous dinosaur footprints from the Molfetta tracksite (Apulia, southern Italy). (February 2023) - Antonelli, Matteo; Petti, Fabio Massimo; Conti, Jacopo; Sacco, Enrico; Petruzzelli, Marco; Spalluto, Luigi; Wagensommer, Alexander
Abstract: The lower Albian track-bearing surface of the San Leonardo quarry (Molfetta, Apulia) is characterised by more than 800 footprints, produced by both quadrupedal and bipedal dinosaurs. Six well-preserved bipedal trackways, composed of tridactyl footprints are attributed to medium-to large-sized theropod dinosaurs. Only one clear but poorly preserved trackway and numerous isolated manus - pes couples have been attributed to quadrupedal dinosaurs. The tridactyl ichnoassemblage, analysed using both traditional methods and close-range photogrammetry, is represented by weakly mesaxonic and robust specimens. Morphological comparison with Upper Jurassic and Lower Cretaceous theropod tracks from surrounding areas, supported by morphometric analyses, points out a highest affinity with the specimens from Switzerland and North Africa. Nevertheless, a set of unique characters appears to justify the establishment of a new ichnospecies, Jurabrontes melphicticus . Additionally, the photogrammetric models of the quadrupedal trackway and four isolated manus - pes sets suggest they belong to the same morphotype, represented by asymmetrical tetradactyl pes and highly digitigrade tetra- or pentadactyl manus . These tracks share numerous morphological characters with both the ichnogenera Tetrapodosaurus and Metatetrapodus and thus can be attributed to a medium-sized ankylosaurian trackmaker.